THE PREVALENCE OF HYDATID CYSTS IN SLAUGHTERED ANIMAL IN IRAQ - Al-Azawi, A.; Al-Taee, S.; Al-Zuhairy, M. (The Iraqi Journal of Veterinary Medicine, 1988)
The prevalence of hydatidosis in sheep, goats and cattle, slaughtered at Baghdad Abattoir, was recorded a period of 14 months. The infection rates were found to be 5.3%, 5%, and 5%, respectively. These rates were generally lower than had been reported in previous studies. The lower prevalence rates were attributed to the elimination of stray dogs, improved standards of meat inspection and the improvement of the living standard. The fertility rate of the cysts was higher in sheep than in goats. All the cattle cysts were sterile.